Conventional ultrasound combined with contrast-enhanced ultrasound quantitative analysis for diagnosing lung cancer metastases in neck lymph nodes - Anran Wang; Mei Zhang; Shufang Xiang; Can Liu (Journal of Men's Health, 2023)
Lung cancer remains one of the most common malignant tumors. Identifying cervical lymph node metastases is important to stage lung cancer, evaluate patients’ prognosis and select appropriate treatments. This study evaluated the utility of conventional ultrasound combined with contrast-enhanced ultrasound (CEUS) quantitative analysis in diagnosing lung cancer metastases in the lymph nodes of the neck. The cervical lymph nodes of 39 patients with primary lung cancer who underwent CEUS and ultrasound-guided needle biopsy were assessed. Routine type B ultrasound was used to record the morphology of the lymph nodes and the presence of lymphatic hilum structure. The Vuebox quantitative analysis software was used to collect lymph node CEUS peak enhancements (PE), rise time (RT) and fall time (FT). The receiver operating characteristic (ROC) curve was used to evaluate the diagnostic value of various parameters and imaging characteristics. The cohort comprised 26 cervical lymph nodes with lung cancer metastasis and 13 cervical lymph nodes with reactive hyperplasia. Most hilum of lymph gland were absent in the metastasis group (92.30%), most lymph nodes showed a full shape (80.77%), and few were irregularly shaped (19.23%). Most hilum of lymph gland were present in the hyperplasia group (76.95%) and showed a full shape (61.54%). The PE of the metastasis group (4852.29 a.u) was significantly lower than the hyperplasia group (11,464.70 a.u), while the difference between RT and FT indicators was not significant. ROC analysis showed that combined PE of the quantitative ultrasound contrast analysis and the presence of the lymphatic phylum structure showed satisfactory diagnostic ability for detecting lung cancer lymph node metastasis in the neck (sensitivity 73.10%, specificity 76.90%, accuracy 48.73%, p = 0.004). Conventional ultrasound observation of lymph node structure combined with quantitative analysis of peak enhancement of contrast-enhanced ultrasound showed promising value for diagnosing lung cancer metastatic lymph nodes.